Cuproptosis as a therapeutic target in cancer: a Systematic Review and bibliometric analysis of the research landscape - Jiang, Chuhan; Xin, Huizhen; Liu, Yuhang; Han, Yangyang (Frontiers in Oncology, 2025)
BackgroundCuproptosis is a new form of cell death induced by intracellular copper overload. With the deepening of research, the research of cuproptosis in the field of cancer has become a hot topic. The bibliometric analysis of cuproptosis research can provide valuable insights into the development of this field.MethodIn this study, the Web of Science Core Collection database was used to obtain literature, and the screened data were imported into CiteSpace software for analysis. We use this data for visualization analysis and made knowledge maps including authors, countries, institutions, journals, and keywords.Results1140 literature was obtained from Web of Science from 2001 to 2024. The results indicate a consistent upward trend in the number of publications in this field. Moreover, a particularly significant surge in the frequency of citations has been observed since 2022. Through a systematic analysis, we found that in the current field of cancer research on cuproptosis, breast cancer, lung cancer, hepatocellular carcinoma and colorectal cancer have more research results.ConclusionThis article describes how copper ions regulate cell death, particularly in cancer therapy, and requires an in-depth understanding of the complexity of copper metabolism and its specific mechanisms of action in cell death. The work provides a panoramic view of the research landscape on cuproptosis in cancer, highlighting its potential as a therapeutic target and the need for further exploration into its mechanisms and clinical applications. With the depth of research, it is expected that cuproptosis will continue to be a hotspot in cancer treatment research. In addition, it provides a solid theoretical foundation and experimental basis for the development of new anti-tumor therapeutic strategies.